Implementation of Dots as the Primary Determinant of Treatment Adherence During the Intensive Phase of Tuberculosis Patients - Ervan Djafar; Margaretha Solang; Vivien Novarina Kasim; Teti Sutriyati Tuloli; Cecy Rahma Karim; Sunarto Kadir (Indonesian Journal of Global Health Research, 2026)
Tuberculosis (TB) remains a major public health burden, particularly in high-incidence countries such as Indonesia. The World Health Organization–recommended Directly Observed Treatment Short-course (DOTS) strategy plays a crucial role in improving treatment success; however, patient adherence during the intensive phase of treatment remains a significant challenge. This study aimed to analyze the relationship between the implementation of the DOTS strategy and adherence to anti-tuberculosis medication during the intensive phase among pulmonary TB patients in Bone Bolango Regency. This study employed a quantitative analytical design with a cross-sectional approach. A total of 75 respondents were recruited using total sampling. Data were collected through a structured questionnaire and analyzed using Chi-square tests and logistic regression analysis. The findings demonstrated significant associations between all DOTS components and treatment adherence, including government commitment (p = 0.006), microscopic examination (p = 0.003), treatment supervision (p = 0.000), drug availability (p = 0.002), and recording and reporting systems (p = 0.004). Treatment supervision was identified as the most dominant factor influencing adherence, with a p-value of 0.001 and an odds ratio (OR) of 0.133 (95% CI: 0.039–0.459). The implementation of the DOTS strategy is strongly associated with adherence to anti-tuberculosis medication during the intensive phase of treatment. Strengthening the role of treatment supervisors, ensuring consistent drug availability, and improving recording and reporting systems are essential to enhance treatment success.